Clinical Analysis of Physiological Drifting of Adjacent Teeth Following Full Crown Preparatio - Rehman, Anis; Sharif, Mubashir; Khalid, Sana; Abbas, Asifa; Bukhari, Syed Junaid Hussain; Abdullah, Ahmed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the physiological drifting of adjacent teeth between young adults versus middle aged patients following full crown preparation.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Prosthodontics, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan from Jun-Dec 2023.Methodology: A total of 140 patients were assessed for inclusion in the study and divided into two groups: Group A (young adult group) and Group B (middle-aged group). Once preparation of tooth to be crowned was completed, inter-space between two teeth adjacent for crowning was measured using a standard digital Vernier caliper by a consultant. Patients were counselled to follow-up for subsequent setting of the crown after 10 days and drifting was checked and measured again before crown placement by digital vernier caliper and endorsed accordingly. Primary variables observed were mesial drifting following pre-crown preparation reviewed after 10 days between both age groups and number of patients requiring re-adjustment for crowning due to change in space.Results: Mean mesial drift post-preparation for crown when assessed at 10 days was 0.04±0.008 mm in the young adult groups versus 0.01±0.006 mm in the middle-aged patient group (p